Enhancing English Language Learning through Digital Mind Mapping: A Comprehensive Approach for Reading Comprehension - Mustakim Sagita; Eva Sulastri Sagita (Yayasan Sagita Akademia Maju, 2024)
This article explores the use of digital mind mapping as a comprehensive tool for enhancing English language learning, with a specific focus on improving reading comprehension skills. Digital mind maps provide a visual and interactive approach to organizing and connecting ideas, fostering deeper cognitive engagement with texts. This study synthesizes existing research on the pedagogical benefits of digital mind mapping, highlighting its ability to support learners in identifying main ideas, tracking relationships between concepts, and developing critical thinking. The article also presents practical strategies for integrating digital mind mapping into English language curricula, emphasizing its role in promoting active learning and learner autonomy. Findings suggest that the use of digital mind maps not only improves reading comprehension but also enhances vocabulary retention, engagement, and motivation. The comprehensive approach outlined in this study aims to provide educators with effective methods for incorporating digital tools to support language acquisition in diverse learning environments.